2004
DOI: 10.1002/chin.200435129
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Acridin‐9‐ylthioureas. Structure, Fluorescence and Biological Properties of Products.

Abstract: It is noteworthy that the reaction of (III) with methyl iodide under alkaline conditions to compounds such as (IV) fails. -(BERNAT, J.; BALENTOVA, E.; KRISTIAN*, P.; IMRICH, J.; SEDLAK, E.; DANIHEL, I.; BOEHM, S.; PRONAYOVA, N.; PIHLAJA, K.; KLIKA, K. D.; Collect. Czech.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…The likely explanation for this is that H-bonding to the sulfur atom by one of these Hs is occurring with resultant formation of a stable five-membered ring (see Scheme 1). Firm confirmation for the presence of an NH 2 group in the major species, and thus the formation of the N-13 methylated product 2, was provided by an 15 N INEPT experiment whereby two hydrogen-bearing nitrogen atoms were readily observed, one of which was discerned to be NH and the other NH 2 . The distinctiveness of the two Hs bound to the same nitrogen was further emphasized by their disparate exchangeability evident from NOESY spectra, thus realizing their assignment.…”
Section: May-jun 2006mentioning
confidence: 99%
See 1 more Smart Citation
“…The likely explanation for this is that H-bonding to the sulfur atom by one of these Hs is occurring with resultant formation of a stable five-membered ring (see Scheme 1). Firm confirmation for the presence of an NH 2 group in the major species, and thus the formation of the N-13 methylated product 2, was provided by an 15 N INEPT experiment whereby two hydrogen-bearing nitrogen atoms were readily observed, one of which was discerned to be NH and the other NH 2 . The distinctiveness of the two Hs bound to the same nitrogen was further emphasized by their disparate exchangeability evident from NOESY spectra, thus realizing their assignment.…”
Section: May-jun 2006mentioning
confidence: 99%
“…(Atomic charges were also calculated at this same level of theory.) The isotropic magnetic shieldings ( ) so obtained were evaluated as chemical shifts ( ) based on their difference from the shieldings of TMS (for both 13 This methodology has been found [32,33,34] to be a reliable and useful method for the calculation of chemical shifts for 15 N, 13 To a solution of acridin-9-yl isothiocyanate [36] (1, 1 g, 4.2 mmol) in methanol (15 mL), methylhydrazine (0.194 g, 0.223 mL, 4.2 mmol) was added dropwise at 0 ºC. The mixture was allowed to stir at room temperature in an atmosphere of nitrogen for 2 h until completion of the reaction as indicated by TLC (benzene/ acetone 5:2).…”
Section: May-jun 2006mentioning
confidence: 99%
“…Bernát et al () reported the synthesis of 9‐acridinyl disubstituted thioureas 5a–j by refluxing appropriate amines with 9‐isothiocyanatoacridine in anhydrous ethanol or at room temperature in chloroform (Fig. ).…”
Section: Synthetic Approaches Of Thioureas Obtained By Isothiocyanatesmentioning
confidence: 99%
“…1-Acridin-9-yl-phenylthiourea was prepared from 9isothiocyanatoacridine and aniline/butylamine by Sinsheimer et al (1975) and 1-acridin-yl-butylthiourea by Deleenheer et al (1973). Bernát et al (2004) reported the synthesis of 9-acridinyl disubstituted thioureas 5a-j by refluxing appropriate amines with 9-isothiocyanatoacridine in anhydrous ethanol or at room temperature in chloroform ( Fig. 4).…”
Section: Synthesis Of Isothiocyanatesmentioning
confidence: 99%
“…For some time our group has been interested to study the synthesis, structure, fluorescence and biological activity of acridine derivatives [7,8,9]. We found it interesting to prove the possible biological synergetic effect by combining the acridine skeleton with other biologically active moieties.…”
Section: Introductionmentioning
confidence: 99%